Imaging Tumor Heterogeneity and the Variations in Nanoparticle Accumulation Using Perfluorooctyl Bromide Nanocapsule X‐Ray Computed Tomography Contrast (Adv. Therap. 8/2022). Issue 8 (18th August 2022) - Beringhs, André O'Reilly; Ndaya, Dennis; Bosire, Reuben; Kasi, Rajeswari M.; Lu, Xiuling
Abstract : Clinical applications of cancer nanomedicines have been challenged by tumor heterogeneity and patient variation. CT imaging of nanoparticle extravasation into solid tumors upon intravenous administration, enabled by this novel nanoparticle contrast, provides critical insights on tumor characteristics and potential for nanoparticle disposition and drug delivery prior to treatment. This is reported by Xiuling Lu and co‐workers in article number 2200047 .